Evaluation of shear bond strength between orthodontic brackets and three aged bulk fill composites = Evaluación de la resistencia de la unión al cizallamiento entre brackets de ortodoncia y tres materiales compuestos de relleno a granel envejecidos - Seyhan Cezairli, Neslihan 1986-; Serkan Küçükekenci, Ahmet; Başoğlu, Hande (2019)
Purpose: The purpose of this study is to evaluate the shear bond strength (SBS) of orthodontic brackets bonded to three different bulk fill composites which were previously aged. Materials and Methods: Three bulk fill composite materials were included in this study (Filtek Bulk Fill, Tetric N-Ceram bulk fill, SureFil SDR bulk fill). Each material group contained 12 samples (n=12); a total of 36 samples were bonded in the same way with maxillary premolar brackets (CB; Avex Mx, OPAL orth.). The same type brackets were bonded on each restored surface made with bulk fill composites. The SBS was examined after storing the specimens for 24 h at 37 ºC indistilled water, followed by thermal ageing (500 cycles between 5 ºC and 55 ºC). Data were analyzed statistically. The numeric data were analyzed using analysis of variance (ANOVA) with Tukey HSD post-hoc tests at α=.05. Results: There were no significant differences among the composite groups (p>0.001). However, SBS values for control group were significantly greater than shear bond strenght values for composite groups (p<0.001). Conclusion: Bond strength of orthodontic brackets on bulk fill composite surfaces was not found adequate. Therefore, this situation leads to bonding failure during orthodontic treatment. The presence of bulk fill composites on the surface to be bonded during orthodontic treatment requires an additional armamentarium.
Propósito: El propósito de este estudio es evaluar la resistencia al cizallamiento (SBS) de brackets de ortodonci unidos a tres compuestos de relleno masivo diferentes que fueron envejecidos previamente. Metodología: Se incluyeron tres materiales compuestos de relleno a granel en este estudio (Filtek Bulk Fill, Tetric N-Ceram bulk fill, SureFil SDR bulk fill). Cada grupo de material contenía 12 muestras (n = 12); un total de 36 muestras se unieron de la misma manera con soportes premolares maxilares (CB; Avex Mx, OPAL orth.). Los mismos soportes de tipo se unieron en cada superficie restaurada hecha con compuestos de relleno masivo. El SBS se examinó después de almacenar las muestras durante 24 horas a 37 ºC de agua no destilada, seguido de un envejecimiento térmico (500 ciclos entre 5 ºC y 55 ºC). Los datos fueron analizados estadísticamente. Los datos numéricos se analizaron mediante el análisis de varianza (ANOVA) con pruebas post hoc de Tukey HSD en α=.05. Resultados: No hubo diferencias significativas entre los grupos compuestos (p> 0,001). Sin embargo, los valores de SBS para el grupo de control fueron significativamente mayores que los valores de resistencia al cizallamiento para los grupos compuestos (p <0.001). Conclusión: La resistencia de de brackets de ortodonci en superficies compuestas de relleno en masa no se encontró adecuada. Por lo tanto, esta situación conduce a una falla de adhesión durante el tratamiento de ortodoncia. La presencia de compuestos de relleno a granel en la superficie a unir durante el tratamiento de ortodoncia requiere un arsenal adicional.
En revista Odóvtos, vol. 21, no. 3 (septiembre-diciembre 2019)
Descripción basada en el contenido visto 06 de septiembre, 2024
También disponible en formato HTML y EPUB
Keywords: ORTODONCIA; RESINAS COMPUESTAS